Electromagnetic Functions of Patterned 2D Materials for Micro–Nano Devices Covering GHz, THz, and Optical Frequency. Issue 19 (22nd July 2019) - Zhang, Min; Wang, Xi‐Xi; Cao, Wen‐Qiang; Yuan, Jie; Cao, Mao‐Sheng
Abstract: 2D materials strongly drive the development of micro–nano devices, and patterned structures based on such crystals bring new opportunities. The advanced fabrication techniques of patterned 2D materials and the analysis of their electronic structures, and physical properties to provide access to diverse applications are discussed. Special attention is given to the hotspot electromagnetic functions and devices based on patterned 2D materials, including photodetectors, optoelectronic switches, modulators, polarization converters, gratings, as well as electromagnetic wave attenuation devices. Finally, a systematical outlook on the development of patterned 2D materials in micro–nano devices is presented, pointing out the current problems and exploring the most promising directions in the future. Abstract : Electromagnetic functions of patterned 2D materials for micro–nano devices are summarized covering GHz, THz, and optical frequency. The advanced fabrication techniques of patterned 2D materials are highlighted. Unique features of the patterned 2D materials, including electronic structures and physical properties, are discussed. A possible inspiration is provided for the design of new micro–nano devices.